Oral health-care system of North Korea and oral health inequalities among North Korean refugees: A narrative review - Yong-Seung Kim; Hoon Myoung (Journal of Korean Dental Association, 2026)
The division of the Korean Peninsula has produced long-standing disparities in health-care systems, yet no nationwide oral health survey of the North Korean population is publicly available. This narrative review synthesized national-level estimates from international organizations, limited studies among children inside North Korea, literature on the North Korean oral health-care system and its marketization, and studies of clinical indices and post-resettlement dental-care access among North Korean refugees, to examine the structural vulnerability of North Korean oral health care and the oral health inequalities that persist after resettlement. Although North Korea officially espouses free medical care and preventive medicine, shortages of medical resources, limited access to restorative and prosthetic treatment, and the expansion of informal fee-based care have been reported. Among refugees, older age groups had a greater proportion of missing teeth within the DMFT index, whereas the filled-teeth component remained low; extensive alveolar bone loss and reduced oral health-related quality of life were also reported. Children from refugee families showed more untreated caries and unmet dental-care needs than South Korean children. After resettlement, cost burden, limited understanding of the health-care system, and low oral health literacy were reported as barriers to dental care. Policy for North Korean refugees should therefore move beyond one-time treatment support toward standardized initial screening, early treatment of untreated caries and periodontal disease, tailored education to improve oral health literacy, sustained linkage for high-cost treatment, and life-course management, providing a basis for oral health policy in preparation for possible inter-Korean health-care exchange and cooperation.